2022
DOI: 10.1155/2022/4671419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endurance Training in COPD Patients Undergoing Pulmonary Rehabilitation: A Meta-Analysis

Abstract: Background. The efficacy of endurance training (ET) on patients with chronic obstructive pulmonary disease (COPD) has been controversial. This study was aimed at meta-analyzing the effect of ET in COPD patients undergoing pulmonary rehabilitation. Methods. The literature retrieval was performed in databases to screen relevant literature. Inclusion criteria were as follows: (1) subjects—COPD patients; (2) inclusion of interventional and control groups; (3) intervention measures—the interventional group received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Several studies have shown that exercise training is the cornerstone of pulmonary rehabilitation as it markedly improves functional performance, muscle mass, and exercise capacity in COPD patients [ 8 , 9 , 10 ]. Endurance exercise training is the most common exercise modality prescribed in COPD [ 11 , 12 , 13 ], which has been shown to improve exercise tolerance and muscle oxidative capacity in these patients [ 12 , 14 , 15 , 16 ]. However, endurance training could also increase oxidative stress levels in severe COPD patients [ 17 ], which may not be desirable as it could impair skeletal muscle function.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that exercise training is the cornerstone of pulmonary rehabilitation as it markedly improves functional performance, muscle mass, and exercise capacity in COPD patients [ 8 , 9 , 10 ]. Endurance exercise training is the most common exercise modality prescribed in COPD [ 11 , 12 , 13 ], which has been shown to improve exercise tolerance and muscle oxidative capacity in these patients [ 12 , 14 , 15 , 16 ]. However, endurance training could also increase oxidative stress levels in severe COPD patients [ 17 ], which may not be desirable as it could impair skeletal muscle function.…”
Section: Introductionmentioning
confidence: 99%